2017
DOI: 10.1093/nar/gkx763
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of mitotic recombination between DNA repeats in centromeres

Abstract: Centromeres that are essential for faithful segregation of chromosomes consist of unique DNA repeats in many eukaryotes. Although recombination is under-represented around centromeres during meiosis, little is known about recombination between centromere repeats in mitotic cells. Here, we compared spontaneous recombination that occurs between ade6B/ade6X inverted repeats integrated at centromere 1 (cen1) or at a non-centromeric ura4 locus in fission yeast. Remarkably, distinct mechanisms of homologous recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…We also observe LOH tracts spanning across the centromere (Figure 2). Since crossovers are suppressed near centromeres in both mitosis and meiosis, our results provide experimental evidence for the occurrence of gene conversions events at centromere locations that are critical for their evolution (Talbert and Henikoff 2010;Thakur and Sanyal 2013;Zafar et al 2017).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We also observe LOH tracts spanning across the centromere (Figure 2). Since crossovers are suppressed near centromeres in both mitosis and meiosis, our results provide experimental evidence for the occurrence of gene conversions events at centromere locations that are critical for their evolution (Talbert and Henikoff 2010;Thakur and Sanyal 2013;Zafar et al 2017).…”
Section: Discussionmentioning
confidence: 65%
“…99 kb) in S/Y and in S/R (204.89 kb from centromeres, 142.93 kb from telomeres) hybrids. However, in some S/Y (e.g., S/Y_8) and S/R lines, the LOH tracts were observed to span the centromere suggesting centromeres are not immune to LOH mediated by mitotic recombination ( Figure 2A, Table S4, Table S5) (Zafar et al 2017).…”
Section: Mutation Accumulation Lines Of S Cerevisiae Hybrid and Homomentioning
confidence: 99%
“…Dnmt3a and Dnmt3b that catalyze DNA methylation, another epigenetic mark of heterochromatin in mammalian cells, suppress recombination at the centromeres 87 . However, our previous study has shown that clr4∆ increases recombination between inverted repeats in the centromeres by ~2-fold 54 , arguing against the notion that clr4∆ merely increases DNA lesions that cause GCRs. Clr4 may affect the choice of recombination pathways at the centromeres.…”
Section: Discussionmentioning
confidence: 90%
“…Loss of ura4 + and ade6 + from ChL results either from translocation, truncation, or isochromosome formation (Fig. 2b) 29,53,54 . Isochromosomes are produced by recombination between inverted repeats at the centromeres.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when recombination happens in silenced chromatin, error-free repair pathways are promoted. In budding yeast for instance, subtelomeric Sir3p-repressed chromatin promotes HR by inhibiting excessive DNA-end resection ( Batté et al 2017 ), and in fission yeast centromeric chromatin Rad51-dependent HR is favored over SSA ( Zafar et al 2017 ). Heterochromatic DSBs also rely largely on HR for their repair in G2 mouse cells ( Beucher et al 2009 ) and in Drosophila cultured cells, where pericentromeric heterochromatin appears to be largely repaired through Rad51-dependent HR ( Chiolo et al 2011 ; Tsouroula et al 2016 ).…”
Section: Impact Of Heterochromatin On Dna Repair Pathway Choicementioning
confidence: 99%